Answer:
???69
Step-by-step explanation:
Answer:
Distributive Property
Step-by-step explanation:
Answer choice a is correct because you are distributing 2 to each term in the parentheses. When you multiply 2 to each factor in the parentheses, it simplifies to 2x-2, thus making the new equation 6x+2x-2=30
Answer:
2.5 dollars
Step-by-step explanation:
Hey there :)
We know the area formula of a triangle
![\frac{1}{2} (base)(height)](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B2%7D%20%28base%29%28height%29)
We are given:
The area = 56 m²
The base = let p represent this
The height = 9 m less than the base = p - 9
Apply the formula
56 =
![\frac{1}{2}](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B2%7D%20)
× ( p ) × ( p - 9 )
56 =
![\frac{1}{2}](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B2%7D%20)
× ( p² - 9p )
Divide
![\frac{1}{2}](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B2%7D%20)
on both sides
56 ÷
![\frac{1}{2}](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B2%7D%20)
= p² - 9p
112 = p² - 9p
Bring 112 to the other side and equate equation to 0
p² - 9p - 112
Factorise { Sum = -9 , Product = - 112 , therefore suitable factors = - 16 × 7 )
( p - 16 )( p + 7 ) = 0
↓ ↓
p = 16 p = - 7 ← Reject p = - 7 since length cannot be negative
So, the length of the base is 16 mCheck:
56 m² =
![\frac{1}{2}](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B2%7D%20)
× 16 × ( 16 - 9 )
56 m² = 8 × 7
56 m² = 56 m²
Answer:
1330
Step-by-step explanation:
Use to formula...
21!/((21-3)!(3!) = 1330